2012
DOI: 10.1590/s2175-78602012000400003
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and genomic characterization of Rhynchospora tenuis complex (Cyperaceae) and its taxonomic implications

Abstract: Species of Rhynchospora sect. Tenues are morphologically very similar. Rhynchospora tenuis complex is the most problematic species complex in this group and it concentrates entities of difficult delimitation, as is the case of R. tenuis, R. tenuis subsp. austro-brasiliensis and R. enmanuelis. Samples of these three taxonomic entities, besides R. junciformis and R. breviuscula (Dichromena), were analyzed in a comparative way using morphologic, cytogenetic and molecular tools. Despite of high morphological simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
1
4
0
2
Order By: Relevance
“…According to Araújo (2001), R. albiceps and R. consanguinea are very similar morphologically and occur sympatrically. In the case of R. junciformis, Michelan et al (2012) found, in addition to morphological similarity, the species also overlaps in cytogenetic characters and molecular markers with R. tenuis, a species found in this work.…”
Section: Resultssupporting
confidence: 74%
“…According to Araújo (2001), R. albiceps and R. consanguinea are very similar morphologically and occur sympatrically. In the case of R. junciformis, Michelan et al (2012) found, in addition to morphological similarity, the species also overlaps in cytogenetic characters and molecular markers with R. tenuis, a species found in this work.…”
Section: Resultssupporting
confidence: 74%
“…However, ISSR markers are more reliable, because the primers are larger and the annealing temperature is higher, which provides a greater specificity (Bornet and Branchard, 2001). ISSR have been used for several purposes, such as phylogenetic inferences (Dogan et al, 2007), evaluation of genetic diversity (Aguilera et al, 2011), and studies of species complexes (Michelan et al, 2012), among others.…”
Section: Introductionmentioning
confidence: 99%
“…The ChromEvol analysis indicated polyploidization as the major driver of genome evolution in Rhynchospora , followed by dysploidy. Ancestral chromosome number reconstruction gave either x = 5 or x = 10 as potential ACN in contrast to the primary number x = 5, reported by classic cytogenetic studies ( Luceño et al., 1998a ; Vanzela et al., 2000 ; Arguelho et al., 2012 ; Michelan et al., 2012 ). If x = 5 is indeed the ACN for Rhynchospora (as suggested by the Bayesian ChromEvol method), then polyploidy could be more relevant than fission/fusion events, although we could not discard other mechanisms.…”
Section: Discussionmentioning
confidence: 56%
“…Tenues seems to have happened via a set of events, starting from 2 n = 10 ( n = 5), reducing to 2 n = 4 ( n = 2; descending dysploidy), and achiasmatic meiosis in R. tenuis ( Vanzela et al., 2003 ; Cabral et al., 2014 ), followed by ascending dysploidy to 2 n = 5, 6, and a possible polyploid with 2 n = 8, also in R. tenuis . Besides, potential polyploidy was responsible for 2 n = 18 found in two other species in the section (see Vanzela et al., 1996 ; Vanzela et al., 2000 ; Arguelho et al., 2012 ; Michelan et al., 2012 ). Except for the potential polyploid cases, we do not see such a sharp contrast in DNA content between diploid and dysploid species of this section.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation